Hummingbird - Davies, Nicola 1958- (Walker Books and Subsidiaries, 2019)
A hummingbird weighs less than a nickel, less than a 20 pence piece, less than a 50 cent bit. Whatever way you use to measure it, it's tiny. But every spring, hummingbirds that have spent the winter in Mexico fly north to make the most of the warmer weather. They nest as far north as Canada and Alaska - a 2,000-mile trip, made by a bird smaller than your thumb. This is the story of one spring migration: of a tiny bird, its amazing journey and the people it meets along the way
Keywords: Hummingbirds / Juvenile literature; Migration / Pictorial works / Juvenile fiction; Hummingbirds; Rubinkehlkolibri; Kolibris; Vogelzug; Bilderbuch